THE INFLUENCE OF IDIOSYNCRATIC VOLATILITY, MARKET RISK, AND SIZE ON STOCK RETURN OF A NON-FINANCIAL COMPANY REGISTERED IN INDONESIA STOCK EXCHANGE IN THE PERIOD OF 2012 – 2016 - Jesslyn Fransisca Darmawan; Werner Ria Murhadi; Putu Anom Mahadwartha (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
The objective of this research is to examine the effect of idiosyncratic volatility, market risk, and size, as the independent variable on stock return on non-financial firm (eight sectoral) listed on Indonesia Stock Exchange. This research uses quantitative perspective with linier regression and model in a panel data for all of the research’s observation used in this research. The number of observation in this research is 1440, consisting of 288 firms that have been enlisted on Indonesia Stock Exchange during 2012-2016 period. The result shows that idiosyncratic volatility has a negative significant effect on stock return. Market risk and size appear to have no significant effect on stock return.